Sensitivity of Melt Pool Size and Porosity Appearing to Base Plate Preheating in Laser Powder Bed Fusion Process - N. Hassine; S. Chatti; L. Kolsi (Annals of "Dunarea de Jos" University of Galati, Fascicle XII, Welding Equipment and Technology, 2022)
The base plate temperature ranks among the crucial building parameters whose effect on melt pool dimensions and porosity defects generation has not been sufficiently discussed in literature. In the current study, with the aim to explore the dependence between melt pool dimensions, porosity defects and base plate preheating, a 3-dimensional thermal finite element model is carried out to create IN718 single beads, at various base plate temperatures. The dimensions of the melt pool behave favourably with the base plate preheating. Indeed, the melt pool depth, width and length increase continuously with the heat of the base plate, from 20 °C to 500 °C. The melt pool width is more responsive to the base plate temperature than the melt pool depth. Numerical results also indicate that the melt dimensions become more responsive to the temperature of the base plate at a slower scan speed. The degree of porosity is predicted under multiple values of base plate temperature and the results show that porosity tends to disappear with further preheating of the base plate. A satisfying accordance between the numerical finding and the experimental results from literature is identified.